2023
DOI: 10.1186/s13037-023-00369-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between patient safety culture and adverse events in Iranian hospitals: a survey among 360 nurses

Abstract: Background Adverse events have become a global problem and are an important indicator of patient safety. Patient safety culture is essential in efforts to reduce adverse events in the hospital. This study aimed to investigate the status of the patient safety culture, the frequency of adverse events, and the relationship between them in Qazvin's hospitals in Iran. Methods The present study is a descriptive-analytical study conducted in six hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
1
0
3
Order By: Relevance
“…The findings showed that 67% of nurses experienced the occurrence of AEs in the past six months. These findings were consistent with a previous study conducted in Iran [ 30 ] which showed the prevalence of AEs was between 33.1 and 51.1%. Song et al in China revealed that the prevalence of AEs was 13.9% of operating room nurses [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…The findings showed that 67% of nurses experienced the occurrence of AEs in the past six months. These findings were consistent with a previous study conducted in Iran [ 30 ] which showed the prevalence of AEs was between 33.1 and 51.1%. Song et al in China revealed that the prevalence of AEs was 13.9% of operating room nurses [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Research related to safety culture in the hospital environment is constantly growing ( 6 - 7 ) , which reinforces the fact that organizational values directly impact safety results, also encompassing the occurrence of adverse events, that is, concrete harm to patient ( 8 ) . Such values need to be strengthened in any care delivery environment, even though it is recognized that some environments have a higher or more evident risk due to the nature of the work processes developed, such as the Surgical Center (SC) ( 9 ) .…”
Section: Introductionmentioning
confidence: 91%
“…Las investigaciones relacionadas con la cultura de seguridad en el ambiente hospitalario están en constante crecimiento ( 6 - 7 ) , lo que refuerza el hecho de que los valores organizacionales impactan directamente en los resultados de seguridad, abarcando también la ocurrencia de eventos adversos, es decir, daños concretos al paciente ( 8 ) . Tales valores deben fortalecerse en cualquier entorno de prestación de atención, aunque se reconoce que algunos ambientes tienen un riesgo mayor o más evidente debido a la naturaleza de los procesos de trabajo desarrollados, como el Centro Quirúrgico (CQ) ( 9 ) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Semakin baik patient safety culture maka semakin rendah insiden keselaman pasien di rumah sakit tersebut. Penelitian lain menyebukan bahwa departemen atau unit kerja dengan budaya keselamatan pasien yang lebih positif memiliki adverse event yang lebih rendah (Hafezi et al, 2022;Binkheder et al, 2023;Muñoz et al, 2023;Moosavi et al, 2023).…”
Section: Pembahasanunclassified